Pre-clinical lung squamous cell carcinoma mouse models to identify novel biomarkers and therapeutic interventions - Sahu, Priyanka; Donovan, Chantal; Paudel, Keshav Raj; Pickles, Sophie; Chimankar, Vrushali; Kim, Richard Y.; Horvart, Jay C.; Dua, Kamal; Ieni, Antonio; Nucera, Francesco; Bielefeldt-Ohmann, Helle; Mazilli, Sarah; et al. (Frontiers in Oncology, 2023)
Primary lung carcinoma or lung cancer (LC) cancer is classified into small-cell or non-smallcell (NSCLC) lung carcinoma. Lung squamous cell carcinoma (LSCC) is the second most common subtype of NSCLC responsible for 30% of all LCs, and its survival remains low with only 24% of patients living for five years or longer, post-diagnosis primarily due to the advanced stage of tumours at the time of diagnosis. The mechanisms of pathogenesis of LSCC is still poorly understood and has hampered the development of effective diagnostics and therapies. This review highlights the known risk factors, genetic and epigenetic alterations, miRNA biomarkers linked to the development and diagnosis of LSCC and the lack of therapeutic strategies to target specifically LSCC. We will also discuss existing animal models of LSCC including carcinogen induced, transgenic and xenograft mouse models, and their advantages and limitations along with the chemopreventive studies and molecular studies conducted using them. The importance of developing new and improved mouse models will also be discussed that will provide further insights into the initiation and progression of LSCC, and enable the identification of new biomarkers and therapeutic targets.